Hybrid Client/Server Peer to Peer Multitier Video Streaming - Ibrahim, Ibrahim Mahmood; Zeebaree, Subhi R. M.; Yasin, Hajar Maseeh; Sadeeq, Mohammed A. M.; Shukur, Hanan M.; Alkhayyat, Ahmed (2021 International Conference on Advanced Computer Applications (ACA), 2021)
Real-Time Video Distribution (RTVD) is now the focus of many applications, including video conferencing, surveillance, video broadcasting, etc. This paper introduces a multi-IP camera-based method for distributing video signals to several levels using a hybrid client/server with peer-to-peer. There are four primary functions in the proposed structure: firstly, all linked camera transmissions will be received by the central server, and video signals will be shown to all attached clients and servers in Level two. The second function means that the clients/servers in level two start viewing received video signals and rebroadcasts them to the next level. The third function is clients/servers in level three who receive the video signals from the upper level and rebroadcast them to the fourth level. The fourth level consists of many clients that start viewing received video signals from level three. Therefore, the planned architecture and mechanism of the proposed system can provide the admin the capability to concentrate on the frames obtained from IP cameras to/from the central server. Furthermore, this mechanism can register and store the stream of frames and encode these frames during transmission. The proposed system depended on VC# programming language as a dependent tool that relied on various architectures and algorithms.